Kepemimpinan Kepala Kampung Dalam Penyelenggaraan Pemerintahan Kampung - Hubertus; Bagasu, Welsen (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
This study aims to describe the leadership of the village head in the implementation of village government in Wasur Village, Merauke Regency. Data collection techniques in the form of observation, interviews and documentation, Data analysis techniques in the form of data presentation, data reduction, and conclusion assessment The results of research on village head leadership in the implementation of village government in Wasur Village, Merauke District have not run effectively in running the village government. This can be seen from the indicators of mobilizing community potential that it is only limited to providing training which is limited both in terms of time and cost, because so far the training has only been aimed at rice farmers and also the managing community. For indicators of the duties of his superior government, the Head of Wasur Village has not fully carried out the duties and responsibilities given to him as the village head, where so far the head of Wasur Village has rarely been in the office, so it is rather difficult to carry out his duties in village government affairs, both development and empowerment matters to the community and other matters entrusted to him, including development affairs. For the indicatot to coordinate the running of the village government, the Village Head still lacks coordination of development activities at the village level and has not optimized all potential development resources, starting from the stages of planning, implementing, supervising, and maintaining development results at the Wasur Village level.